Pengembangan Agrowisata Merah Jambu Berbasis Wisata Edukasi Di Kabupaten Karanganyar - Silfi Amalia Chusna; Made Prasta Yostitia Pradipta; Erna Sadiarti Budiningtyas (SABBHATÃ YATRA : Jurnal Pariwisata dan Budaya, 2022)
This study aims to find out what developments should be done by Merah Jambu Agrotourism in order to become an education-based Agrotourism in Karanganyar Regency. Through education-based agro-tourism development efforts, it is hoped that it can help improve the economy of the community around the agro-tourism area and education can become a new attraction that can attract tourists. In this study, the author uses a qualitative descriptive method. Data collection techniques were carried out by means of library research, observation, interviews and documentation, data analysis techniques used were data reduction, data presentation and conclusion drawing. Next, test the validity of the data in this study using the triangulation technique. Based on the results of the study, it can be found that the problems that exist in the Merah Jambu Agrotourism are the absence of attractions and also the lack of facilities in the Merah Jambu agrotourism. Therefore, the need for agro-tourism development as in the tourism development theory by Cooper, namely A4 (Attractions, Accessibility, Amenity, and Ancillary) and the development of education-based attractions in agro-tourism in the form of agricultural education tourism systems in plantation areas and the use of restaurants as facilities for workshops can be realized. by Merah Jambu Agrotourism to become an education-based Agrotourism in Karanganyar Regency.